Dynamic changes in the direction of blood flow through the ductus arteriosus at birth - Crossley, Kelly J (Blackwell Science Inc, 2009)
Major cardiovascular changes occur at birth, including increased pulmonary blood flow (PBF) and closure of the ductus arteriosus (DA), which acts as a low resistance shunt between the fetal pulmonary and systemic circulations. Although the pressure gradient between these circulations reverses after birth, little is known about DA blood flow changes and whether reverse DA flow contributes to PBF after birth. Our aim was to describe the changes in PBF and DA flow before, during and after the onset of pulmonary ventilation at birth. Flow probes were implanted on the left pulmonary artery (LPA) and DA in preterm fetal sheep (n= 8) ∼3 days before they were delivered and ventilated. Blood flow was measured in the LPA and DA, before and after umbilical cord occlusion (UCO) and for 2 h after ventilation onset. Following UCO, DA flow decreased from 534 ± 57 ml min(−1) to 237 ± 29 ml min(−1) which reflected a similar reduction in right ventricular output. Within 5 min of ventilation onset, PBF increased from 11 ± 6 ml min(−1) to 230 ± 13 ml min(−1) whereas DA flow decreased to −172 ± 54 ml min(−1); negative values indicate reverse DA flow (left-to-right shunting). Reverse flow through the DA contributed up to 50% of total PBF at 30 min and a decrease in this contribution accounted for 71 ± 13% of the time-related decrease in PBF after birth. DA blood flow is very dynamic after birth and depends upon the pressure gradient between the pulmonary and systemic circulations. Following ventilation, reverse DA flow provided a significant contribution to total PBF after birth.